If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+-3=7+9x
We move all terms to the left:
4x+-3-(7+9x)=0
We add all the numbers together, and all the variables
4x-(9x+7)-3+=0
We add all the numbers together, and all the variables
4x-(9x+7)=0
We get rid of parentheses
4x-9x-7=0
We add all the numbers together, and all the variables
-5x-7=0
We move all terms containing x to the left, all other terms to the right
-5x=7
x=7/-5
x=-1+2/5
| 2x-8*4=5 | | -10+12,5y+8+2,5y=14,5y+8 | | -10+12,5y+8+2,5y=14,6+8 | | (x-7)²=(x+4)² | | 3x/8+5x-16/8=x-2 | | 5/2x+7/3x=11/6x | | 12+x=6+4x | | 12+x=6-4x | | 3+1m=3m-14444 | | 137-u=203 | | 5-5x5+5=-25 | | 2(2x+1)+4=6(3x-6 | | x-(-15)=6 | | -3*x+20=x | | 6*(x-2)=-1*x+23 | | 2*(x+4)=20 | | 2*x+4=-4*x+34 | | 2*x+4=−4*x+34 | | 2*x-6=-16 | | 5y+4y=23 | | (10^2x)/10=100 | | 2x-x-5+7=12 | | 1/3x=2x15 | | 13w-6w=14 | | x+12+x-12=180 | | 2x~+7=3+1 | | x/3=8=-2 | | 5/6×1=x | | 5x=3x-40 | | 40=5(x-90 | | (2x)*x=66 | | 9x(+5)=-9 |